Feasibility and Compatibility of Minilaparotomy Hysterectomy in a Low-Resource Setting - Abhilasha Agarwal; Jyothi Shetty; Deeksha Pandey; Gazal Jain (Obstetrics and Gynecology International, 2018)
Introduction. Minilaparotomy hysterectomy (MLH) relies on the simplicity of the traditional open technique of abdominal hysterectomy, imparts cosmesis and faster recovery of laparoscopic hysterectomy yet avoids the long learning curve and cost of expensive setup and instrumentation associated with the minimally invasive approaches, namely, laparoscopy and robotics. In the present study, we tried to ascertain whether the results obtained with MLH can be compared to LAVH in terms of its feasibility, intraoperative variables, and complications. The null hypothesis was that both MLH and LAVH are comparable techniques; thus, where cost and surgeon’s experience are the confining issues, patients can be reassured that MLH gives comparable results. Materials and Methods. This was a prospective observational study done over a period of two years at a university teaching hospital. A total of 65 patients were recruited, but only 52 (MLH: 27; LAVH: 25) could be included in final analysis. All surgeries were performed by one of the two gynecologists with almost equal surgical competence, and outcomes were compared. Results. MLH is a feasible option for benign gynecological pathologies as none of the patients required increase in the initial incision (4–6 cm). MLH could be done for larger uteri (MLH: 501.30 ± 327.96 g versus LAVH: 216.60 ± 160.01 g; p<0.001), in shorter duration (MLH: 115.00 ± 21.43 min versus LAVH 172.00 ± 27.91 min; p<0.001), with comparable blood loss (MLH: 354.63 ±227.96 ml; LAVH: 402.40 ± 224.02 ml; p=0.334), without serious complications when compared to LAVH. Conclusion. The technique of MLH should be mastered and encouraged to be used in low-resource setting to get results comparable to laparoscopic surgery. This trial is registered with NCT03548831.